The Effectiveness Of The Keluarga Harapan Program In The Welfare Of The Community In Oti Village Sindue Tobata District Donggala Regency - Nafia, Mar'atun; Tawil, Muzakir; Salingkat, Syarif (JPS: Journal of Publicness Studies, 2024)
This study aims to determine the effectiveness of family programs hope in the welfare of the community in Oti village, Sindue Tobata district Donggala county. This research uses Richard M.Steers's theory that includes three indicators of goal achievement, integration, and adaptation. The basis and type of this research is Qualitative Descriptive research, techniques Purposive sampling of informants by the number of informants a total of five people, the data collection technique used is observation (observations), interviews and documentation to collect data that It is needed in the form of primary and secondary data. Data analysis performed with data collection, data condensation, data presentation, and conclusion drawing. The results of the research on the aspect of achieving goals in terms of the timing of the implementation of the program have been running, but there are time constraints on its implementation where there is a delay in disbursement of PKH funds, and in terms of PKH assistance targets are also not effective because in choosing prospective PKH beneficiaries is not in accordance with existing criteria. In the integration aspect of the implementers and persons in charge of the PKH assistance program, it has not run optimally because PKH recipients who often do not attend group meetings and PKH assistants who do not routinely socialize once a month as appropriate. And in the aspect of adaptation, it has also not run effectively when viewed from the human resources of the PKH assistance program implementers who cannot carry out the assistance in accordance with the criteria.